2018
DOI: 10.1371/journal.pone.0207909
|View full text |Cite
|
Sign up to set email alerts
|

Peer-assisted learning after onsite, low-dose, high-frequency training and practice on simulators to prevent and treat postpartum hemorrhage and neonatal asphyxia: A pragmatic trial in 12 districts in Uganda

Abstract: An urgent need exists to improve and maintain intrapartum skills of providers in sub-Saharan Africa. Peer-assisted learning may address this need, but few rigorous evaluations have been conducted in real-world settings. A pragmatic, cluster-randomized trial in 12 Ugandan districts provided facility-based, team training for prevention and management of postpartum hemorrhage and birth asphyxia at 125 facilities. Three approaches to facilitating simulation-based, peer assisted learning were compared. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 32 publications
9
93
0
Order By: Relevance
“…Similar studies done in Ghana and Uganda (7,8) showed promising results with the onsite simulationbased low-dose, high-frequency (LDHF) plus mobile (m)-mentoring training approach. In these studies health workers competencies were better with the LDHF+mMentoring approach compared with the TRAD approach although limited skills were assessed such as newborn resuscitation and postpartum haemorrhage (PPH).…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Similar studies done in Ghana and Uganda (7,8) showed promising results with the onsite simulationbased low-dose, high-frequency (LDHF) plus mobile (m)-mentoring training approach. In these studies health workers competencies were better with the LDHF+mMentoring approach compared with the TRAD approach although limited skills were assessed such as newborn resuscitation and postpartum haemorrhage (PPH).…”
mentioning
confidence: 66%
“…The acquisition and retention of BEmONC skills was different at 12 months with the LDHF/m-mentoring arm demonstrating better performance than the TRAD arm. This study contributes to the much needed evidence base for LDHF/m-mentoring training approach in LMICs, adding on the finding of related studies done in Uganda [7] and Ghana [8]. As part of the intervention package, LDHF/m-mentoring study arm participants received weekly SMS reminders and quizzes along with continuous skills practice on anatomical models, which helped, reinforce knowledge on specific clinical areas over time.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…One training modality that has been reported to signi cantly in uence the uptake and performance of other maternal and neonatal life-saving procedures is the use of low-dose high-frequency skills-building sessions. Studies in Ghana, Tanzania and Uganda reported improved knowledge and skills of providers and better maternal and perinatal outcomes when providers were trained through simulation, case-based learning and small content packages spread over short time intervals (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%